APPLICATION OF WATER COLOUR PAINT INCORPORATED WITH ESSENTIAL OILS AGAINST TRAMETES VERSICOLOR ON RUBBERWOOD - Narumol, M. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Antifungal activities of water colour paint incorporated with cinnamon oil, clove oil, anise oil, citronella oil, orange oil, tangerine oil, turmeric oil, guava leave oil, nutmeg oil and lime oil against a white-rot decay fungus (Trametes versicolor) identified from rubberwood were investigated. The agar dilution method was employed to determine the minimal inhibitory concentration (MIC) by mixing water colour paint with essential oil at ratios 1:1, 1:2 and 1:4. It was found that cinnamon oil, clove oil and anise oil were the strongest inhibitors with the MICs of 1:4. Decay fungi test of T. versicolor on treated rubberwood (spray with water colour paint incorporated with essential oils at ratio 1:1, 1:2, 1:4) was then conducted according to the ASTM D1413-05b. After 12 weeks of exposure at 25Â°C and 100%RH, the average weight loss of each rubberwood sample was determined. The results indicated that rubberwood treated with water colour paint incorporated with cinnamon oil, clove oil and anise oil at ratio 1:4 were classified as “highly resistant”. These findings suggested that water colour paint incorporated with essential oil has good potential for protecting rubberwood products from the attack of T. versicolor.